Optimization of Employee Task Assignments Using the Hungarian Method and POM-QM at Serupa Cafe - Ninia Lina, Tirsa; Rumetna, Matheus Supriyanto; Karay, Jeni; Hetharia, Charliany; Tindage, Jalmijn (CV.RIZANIA MEDIA PRATAMA, 2025)
This study aims to optimize employee task assignments at Serupa Café, which faces issues of workload imbalance and inefficient task completion times. The research gap lies in the limited application of algorithm-based optimization methods within human resource management in the food and beverage service sector. To address this, the study applies the Hungarian Method, an algorithmic approach with a time complexity of O(n³), to determine the most efficient pairing between employees and tasks. The computation and validation processes were carried out using the POM-QM for Windows software as a quantitative analysis tool. The results indicate that the optimal assignment configuration achieved a total completion time of 85 minutes, with complete consistency between manual and software-generated results. System testing demonstrated high computational efficiency and no logical errors during data processing. Therefore, this study concludes that integrating the Hungarian Method with POM-QM significantly enhances operational performance and contributes to the application of informatics techniques for optimizing human resource management within the service industry.